Development of the TBI-QOL Headache Pain Item Bank and Short Form. Issue 5 (September 2019) - Tulsky, David S.; Tyner, Callie E.; Boulton, Aaron J.; Kisala, Pamela A.; Heinemann, Allen W.; Roth, Elliot J.; Carlozzi, Noelle E.
Abstract : Objective: To develop, calibrate, and evaluate the test-retest reliability of a new patient-reported outcome measure of headache pain relevant for individuals with traumatic brain injury (TBI). Setting: Six TBI Model Systems rehabilitation centers in the United States. Participants: Adults with medically confirmed documentation of TBI. Design: Cross-sectional calibration field testing and test-retest reliability analyses. Main Measures: Traumatic Brain Injury—Quality of Life Headache Pain item bank. Results: Thirteen headache pain items were calibrated as a unidimensional measure using data from 590 participants. The new measure was reliable (α = .98; item-total correlation range: 0.71-0.91). Item parameter estimates were estimated using Samejima's Graded Response Model and a 10-item calibrated short form was created. Simulation testing confirmed that both the computer-adaptive test and the short-form administrations were equivalent to the full item bank. One- to-2-week test-retest reliability of the computer-adaptive test was high (Pearson r and intraclass correlation coefficients = 0.81). Approximately two-thirds of the sample reported at least 1 headache symptom. Conclusion: The Traumatic Brain Injury—Quality of Life Headache Pain item bank and short form provide researchers and clinicians with reliable measures of the subjective experience of headache symptoms for individuals with a history of TBI. Abstract : Supplemental Digital Content is Available in the Text.